Lipase in Enzymatic Palm Biodiesel Production - Renita Manurung (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
Enzymatic biodiesel production process was done by using palm oil as CPO (Crude Palm Oil) as the main raw material in which the first step was screened the enzym that will be used at the next process. The enzyme that we used in screening process was Lipase Candida Antarctica Novozyme 435 and Lipase Mucor miehei Lipozyme IM. The screening process was conducted in 4 run experiments as the CPO was divided into 2 treatments, with and without degumming. As the results of the whole experiments, it was obtained that the highest yield was shown by Candida Antarctica Novozyme 435 with 86,2 %. While Lipase Mucor miehei Lipozyme IM was only able to produce the highest yield of 42 % .